TINGKAT INFESTASI CACING SALURAN PENCERNAAN PADA KAMBING DI GABUNGAN KELOMPOK TERNAK MENDO SEWU DI KECAMATAN SUKOHARJO KABUPATEN PRINGSEWU - Ismail Haryanto; Purnama Edy Santosa; Erwanto Erwanto; Ali Husni; Johan Arfianto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
The study which was conducted at a goat farm belonging to a livestock group of Mendo Sewu in Sukoharjo District, Pringsewu Regency, Lampung Province in February-April 2021 aimed to determine the level of intestinal worm infestation in goats. This study used a survey method with data sampling was done by proportional method. The number of samples obtained was 85 samples. The data obtained were presented in tabulated form and then analyzed descriptively. Examination of faecal samples was carried out at the Lampung Veterinary Center using the Mc. Master and Sedimentation. The results showed that the level of intestinal worm infestation in goats kept by livestock groups in Sukoharjo District was 67.05%. The highest worm infestation was found in goats reared by the Mekar 4 and Sidomakmur livestock groups with a value of 81.25%, while the lowest worm infestation was found in goats reared by the Rukun Amri Sentosa livestock group, which was 58.49%. The types of worms found in goats kept by livestock groups in Sukoharjo District were from the Nematoda class (Haemonchus sp., Oesophagostomum sp., Trichostrongylus sp., Strongyloides sp., and Trichuris sp.), Cestoda class (Moniezia sp.), and Trematodes (Fasciola sp.). Gastrointestinal worm infestation rate found in goats reared by Mekar 4, Sidomakmur and Rukun Amri Santosa livestock groups were in a high digestive worm infestation rate of 67.05%. Keywords: Gastrointestinal worms, Goat, Infestation rate